2017
DOI: 10.3233/jad-170304
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Oxidative Stress and Microvasculature Defects in TNF-α Expressing Transgenic and Porphyromonas gingivalis-Infected ApoE–/– Mice

Abstract: The polymicrobial dysbiotic subgingival biofilm microbes associated with periodontal disease appear to contribute to developing pathologies in distal body sites, including the brain. This study examined oxidative stress, in the form of increased protein carbonylation and oxidative protein damage, in the tumour necrosis factor-α (TNF-α) transgenic mouse that models inflammatory TNF-α excess during bacterial infection; and in the apolipoprotein knockout (ApoE wild-type and TNF-α transgenic mice. This study revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 56 publications
1
33
0
1
Order By: Relevance
“…In order to investigate the contribution of peripheral inflammatory responses on oxidative stress in the brain, Rokad et al infected TNF-α transgenic mice with P. gingivalis . These mice express a stabilized version of TNF-α mRNA, resulting in overexpression of TNF-α protein in most tissues, including the brain (Rokad et al, 2017). In these mice, P. gingivalis infection increased the proportion of oxidized proteins in whole brain lysates, suggesting that P. gingivalis may contribute to cellular damage and downstream protein oxidation.…”
Section: Bacterial Pathogens Associated With Neurodegenerationmentioning
confidence: 99%
“…In order to investigate the contribution of peripheral inflammatory responses on oxidative stress in the brain, Rokad et al infected TNF-α transgenic mice with P. gingivalis . These mice express a stabilized version of TNF-α mRNA, resulting in overexpression of TNF-α protein in most tissues, including the brain (Rokad et al, 2017). In these mice, P. gingivalis infection increased the proportion of oxidized proteins in whole brain lysates, suggesting that P. gingivalis may contribute to cellular damage and downstream protein oxidation.…”
Section: Bacterial Pathogens Associated With Neurodegenerationmentioning
confidence: 99%
“…In support of this hypothesis, P. gingivalis infected animal models demonstrated hippocampal damage via inflammation-mediated injury and IgG and gingipains in the cerebral microvasculature (Singhrao et al, 2017 ). In addition, the phagocytic oxidative burst of the host’s neutrophils and macrophages at a much earlier time point of P. gingivalis infection, and the oxidative stress response initiated by bacteria can equally damage the hippocampal microvasculature (Rokad et al, 2017 ). A permeable BBB also has implications for entry of extra-cerebral amyloid/amyloid-like proteins to the brain and add to the existing amyloid burden.…”
Section: Senile Plaque a Miniature Biofilm Hypothesismentioning
confidence: 99%
“…All are potential causes for the development of sporadic AD. P. gingivalis was shown to migrate from its oral location to the brain [54,55] where it invoked inflammatory responses typical of neurodegenerative diseases in mice with blood–brain barrier (BBB) damage [55,56]. Ishigami et al [57] identified glial fibrillary acidic protein (GFAP), a marker of astrocytes in the AD brain, to be a substrate for host PAD2, and suggested a role for the citrullinated GFAP in the progression of this neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 99%